Unraveling molecular effects of ADAR1 overexpression in HEK293T cells by label-free quantitative proteomics. Issue 12 (17th June 2016) - Guo, Jisheng; Wang, Xiaoyue; Lü, Xin; Jing, Ruirui; Li, Junqiang; Li, CuiLing; Wang, Daoguang; Bi, Baibin; Chen, Xinjun; Wang, Fengqin; Sun, Shengnan; Gong, Jing; et al.
ABSTRACT: ADAR1 is a double-stranded RNA (dsRNA) editing enzyme that specifically converts adenosine to inosine. ADAR1 is ubiquitously expressed in eukaryotes and participate in various cellular processes such as differentiation, proliferation and immune responses. We report here a new proteomics study of HEK293T cells with and without ADAR1 overexpression. The up- and down-regulated proteins by ADAR1 overexpression are identified by liquid chromatography-tandem mass spectrometry (LC-MS/MS) followed by label-free protein quantification. Totally 1, 495 proteins (FDR < 0.01) are identified, among which 211 are up- and 159 are down-regulated for at least 1.5-fold (n = 3, p < 0.05). Gene ontology analysis reveals that these ADAR1-regulated proteins are involved in protein translation and cell cycle regulation. Bioinformatics analysis identifies a closely related network consistent for the protein translation machinery and a tightly connected network through proliferating cell nuclear antigen (PCNA)-interactions. Up-regulation of the proteins in the PCNA-mediated cell proliferation network is confirmed by Western blotting. In addition, ADAR1 overexpression is confirmed to increase cell proliferation in HEK293T cells and A549 cells. We conclude that ADAR1 overexpression modulates the protein translation and cell cycle networks through PCNA-mediated protein-protein interaction to promote cell proliferation in HEK293 cells.